The importance of software engineering code of ethics in a university of technology teaching environment - Hans, R. T.; Marebane, S.; Coosner, J. (South African Journal of Higher Education, 2023)
Computing educators contribute immensely to the development of software engineering graduates, not only in terms of teaching technical skills, but also in ethical development. Positive consideration of software engineering codes of ethics by teachers promotes inclusion in teaching of software development courses. The aim of this study is to investigate the perceived importance of codes of ethics by lecturers who teach software development courses in a university of technology in South Africa. The data was collected using an online survey from 103 educators from two computing departments in a South African UoT; and 44 responses were received. Data was analysed using a t-test to evaluate the difference in responses; and the Pearson Chi-square test was applied to assess the level of association between variables of interest for more conclusive results in addressing the objective of the study. The results of this study indicated that the majority of participants were males; female participants amounted only to 18.2%. Results also reported the majority (95%) of the participants agreeing that lecturers should teach their students the importance of ethical behaviour. SEs have the ability to do good or cause harm with the software products they produce; and SEs have an obligation to reflect on the ethical impact of their software products (p-value<0,05). In addition, an association was presented between the importance of a software engineering code of ethics to a lecturer, and the obligation for SEs to consider ethical implications of their systems. Another statistically significant association between gender and the importance of a software engineering code of ethics to lecturers was shown by the results of the study. This study recommended that the institution consider finding permanent ways of inculcating a culture of ethical conduct into its staff members, encouraging educators to take up professional memberships with professional bodies. These measures will ensure that software development educators are trained to maintain high standards within their profession, embracing the use and adherence to code of ethics in software development.